Ophiopogon wangii (Asparagaceae), a new species from Guangxi, Southern China - Xu, Ting; Qin, Yonghua; Yu, Shengxiang; Jiang, Rihong; Feng, Huizhe (Phytotaxa, 2026)
Ophiopogon wangii, a new species from Guangxi in southern China, is described and illustrated. It resembles other members of the genus with connate stamens, particularly O. szechuanensis, but can be distinguished by its thicker rhizome (ca. 2 cm in diam.), pedicel articulated near the middle, short conical anthers, globose flower buds, and half-inferior ovary with a convex upper surface. The species is currently known only from a single population in a shaded, humid river valley within evergreen broad-leaved forest and is considered Critically Endangered given its extremely restricted distribution and small population size. A detailed morphological description, along with information on habitat, phenology, and taxonomic comparisons, is provided to facilitate further research and conservation of Ophiopogon diversity.